Analisa Kinerja Ruas Jalan Inspektur Yazid Kabupaten Lahat - Sarwandy, M. Hijrah Agung; Agustini, Marice; Miranda, Ade Tricia; Malvariansyah, Osa (Universitas Muhammadiyah Palembang, 2025)
Inspector Yazid Road is one of the important routes often used by vehicles in Lahat District, Lahat Regency. Especially in the lower market area of Lahat, various problems often arise in traffic conditions. Activities in the market have a major impact on the increasing number of daily activities and are one of the main factors causing high traffic volumes. Various side obstacles also worsen the performance of the road section. Referring to the problems that have been mentioned, the author tried to conduct a study to assess and analyze the performance of the Inspector Yazid road section using the 2023 Indonesian Road Capacity Guidelines (PKJI). The data collected included road geometry, vehicle flow, side obstacles, and population in Lahat Regency. The data was then analyzed based on the 2023 Indonesian Road Capacity Guidelines. The results of the study showed that peak times occurred on Monday to Friday between 16.00 and 17.00 WIB, with a vehicle volume reaching 1537 smp/hour, side obstacles 1122 kej/hour, and a capacity of 1837 smp/hour. The free flow speed was recorded at 49.92 km/h, travel speed at 13.64 km/h, and the degree of saturation at 0.84, which indicates that traffic on Jalan Inspector Yazid is in an unstable condition and is almost approaching the maximum capacity limit.